The peculiarities of particle dynamics in the Fermi acceleration scheme - Buts, V.A. (Вопросы атомной науки и техники, 2015)
With examples of discrete and distributed mathematical models of the Fermi acceleration mechanism, a usefulness, or even necessity, of taking into account of singular solutions is demonstrated. Also the role is shown of those parts of phase space where the uniqueness theorem conditions to form the dynamics of physical systems are broken. It was found that the dynamics of particles in discrete and distributed mathematical schemes of Fermi acceleration can be significantly different. The difference is due to the fact that the distributed model takes into account the effects of phase space where conditions do not correspond to those necessary for application of the uniqueness theorem. The role of singular solutions is under discussion as well. На прикладах дискретної та розподіленої математичних моделей механізму прискорення Фермі показана корисність, а в деяких випадках, і необхідність врахування особливих рішень. Також показана роль впливу областей фазового простору, в яких порушуються умови виконання теореми єдності на динаміку досліджуваних фізичних систем. Показано, що динаміка частинок у розподіленій та дискретній схемах прискорення Фермі може істотно відрізнятися. Ця відмінність пов'язана з урахуванням у розподіленій моделі впливу областей фазового простору, у яких порушена теорема єдності. Обговорюється роль особливих рішень. На примерах дискретной и распределенной математических моделей механизма ускорения Ферми показана полезность, а в некоторых случаях, и необходимость учета особых решений. Также показана роль влияния областей фазового пространства, в которых нарушаются условия выполнения теоремы единственности на динамику изучаемых физических систем. Показано, что динамика частиц в распределенной и дискретной схемах ускорения Ферми может существенно отличаться. Это различие связано с учетом в распределенной модели влияния областей фазового пространства, в которых нарушена теорема единственности. Обсуждается роль особых решений.